1996
DOI: 10.1897/1551-5028(1996)015<2240:eopahc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Polycyclic Aromatic Hydrocarbon Concentrations in the Water Column Based on Tissue Residues in Mussels and Salmon: An Equilibrium Partitioning Approach

Abstract: Abstract-Equilibrium partitioning was used to estimate concentrations of dissolved polycyclic aromatic hydrocarbons (PAHs) in the water column from PAH residues in tissues of mussels and juvenile pink salmon collected from coastal marine waters affected by the Exxon Valdez oil spill. Estimated concentrations were within factors of 2 to 5 for fish and 5 to 10 for mussels of average total dissolved and particulate PAHs measured in concurrent water samples. Temporal trends of estimated and measured watercolumn PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 36 publications
5
68
0
Order By: Relevance
“…After of the caged mussels to the effluent plume after diversion. The observed increases in tChlordane and tPAH are consistent with changes expected based on theoretical bioaccumulation equations (Pruell et al 1986, Bergen et al 1993, Neff and Burns, 1996 and applied to the MWRA data by Hunt et al (2002a).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…After of the caged mussels to the effluent plume after diversion. The observed increases in tChlordane and tPAH are consistent with changes expected based on theoretical bioaccumulation equations (Pruell et al 1986, Bergen et al 1993, Neff and Burns, 1996 and applied to the MWRA data by Hunt et al (2002a).…”
Section: Resultssupporting
confidence: 88%
“…The first is that caged mussels "equilibrate" with surrounding water within the 60-day deployment period. As noted above, common understanding among investigators is that 60 days is sufficient for these organisms to adjust to the exposure levels experienced at the deployment sites (ASTM, 2001;Axelman et al, 1999;Baussant et al, 2001;Durell et al 2006;Neff and Burns, 1996;Peven et al 1996;Prest et al, 1992;Salazar and Salazar, 1995). A second assumption is that analytical differences between the programs are minor.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, d 10 -fluoranthene was used as a surrogate standard, which was also adopted by other researchers because the compound showed similar physicochemical properties with musks such as logarithm octanol-water partition coefficient (5.22 for d 10 -fluoranthene [6] and 4-6 for musks [26,27]). To verify the suitability of d 10 -fluoranthene as a surrogate standard for all of synthetic musk compounds during the above pretreatment, the recovery experiments (1.5 mg/L, n ¼ 6) were conducted.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…In 1993, the German detergent industry voluntarily stopped using MX in their products [4,5]. Now, only a small amount of MK and MX is still used, and it is reported that HHCB, AHTN, MK, and MX represent approximately 95% of the market in Europe for all nitro and polycyclic musk fragrances [2,6]. In China, the use of nitro musk fragrances were also restricted by the Chinese government according to the Tenth Five-Year Plan of Light Industry in 2001 [7].…”
Section: Introductionmentioning
confidence: 99%
“…naphthalene) to around 7 for the heavier 19 compounds (e.g. indeno(1,2,3,cd)pyrene) (Mackay, 2006;Neff and Burns, 1996). Many 20 authors have found a linear relationship between log K ow and log bioconcentration factor 21 (BCF) (Hawker and Connell, 1986;Mackay, 1982;Veith et al, 1979) indicating that 22 bioaccumulation is linked to hydrophobicity for a given PAH compound.…”
mentioning
confidence: 99%